2012
DOI: 10.1097/01.asw.0000422625.17407.93
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Reducing Insoles to Prevent Foot Ulceration in High-Risk Diabetic Patients

Abstract: These results suggest that a shear-reducing insole is more effective than traditional insoles to prevent foot ulcers in high-risk persons with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 25 publications
2
91
0
1
Order By: Relevance
“…Effect sizes were large (46.1–63.6% relative risk reduction compared with standard of care therapeutic footwear), but 95% CIs show that effect may vary across patients. These data confirm earlier findings in three RCTs with mixed methodological quality on the efficacy of therapeutic footwear (relative risk reductions compared with control condition: 52.5–70.2%) . One other RCT at low risk of bias assessed the effect of therapeutic insoles and showed no significant effect on ulcer recurrence compared with standard footwear (relative risk reduction 12%) .…”
Section: Therapeutic Footwearsupporting
confidence: 86%
“…Effect sizes were large (46.1–63.6% relative risk reduction compared with standard of care therapeutic footwear), but 95% CIs show that effect may vary across patients. These data confirm earlier findings in three RCTs with mixed methodological quality on the efficacy of therapeutic footwear (relative risk reductions compared with control condition: 52.5–70.2%) . One other RCT at low risk of bias assessed the effect of therapeutic insoles and showed no significant effect on ulcer recurrence compared with standard footwear (relative risk reduction 12%) .…”
Section: Therapeutic Footwearsupporting
confidence: 86%
“…An RCT with high risk of bias by Lavery et al found in 299 patients, of whom 26% had prior ulcers, that insoles designed to reduce shear stress and were worn in extra‐depth therapeutic shoes show a trend but do not significantly reduce ulcer incidence after 18 months compared with standard insoles: 2.0% vs 6.7% ( p = 0.08) . Another RCT with high risk of bias from Rizzo et al involved the initial randomization of 298 patients, 20% with previous ulceration, to intensive footwear therapy based on a prescription algorithm or standard care consisting of footwear advice but no footwear prescription.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has suggested that shear-reducing insoles are helpful for preventing DFU in high-risk persons [13]. In contrast, a study on active DFU that compared a removable cast walker containing a shear-reducing foot bed to two other offloading modalities found the shear-reducing cast walker yielded the lowest healing and highest rate of attrition [14].…”
Section: Achieving Optimal Offloadingmentioning
confidence: 99%